Von Baden bis Troia: Ressourcennutzung, Metallurgie und Wissenstransfer : eine Jubiläumsschrift für Ernst Pernicka - Bartelheim, Martin; Horejs, Barbara; Krauß, Raiko (Oriental and European archaeology, 2016)
This anniversary volume is in honor of Ernst Pernicka, who has made significant contributions to scholarship on metals and their sociocultural aspects. The contributions collected here explore material resources and their cultural aspects in prehistoric societies, focusing on the region between central Europe and the Mediterranean Sea during the Copper and Bronze Ages, with particular emphasis on the key locations Baden and Troy. Topics discussed include Bohemian and Moravian mineral deposits, the role of silver as a medium of social representation in the European Copper Age, possible causes for technological changes in the metalwork of southern Europe in the Copper and Bronze Ages, the use of Caucasian gold in the 4th and 3rd millennia, the introduction of a new system of weights at the beginning of the Bronze Age, and current research on Troy and its role in the 3rd and 2nd millennia